Analysis Of Morphometric Indicators Of The Structural Units Of The Lung Tissue Of Premature Newborns With Respiratory Distress Syndrome (Texas Journal of Medical Science, 2025)
In this scientific study, an analysis of the morphometric parameters of the structural units of the lung tissue in premature infants with hyaline membrane disease was carried out. The lung tissue of premature babies aged 22-37 weeks was taken as a material. Morphometric study of the structural units of the lung tissue was carried out by modifying the method of "counting points" by transferring it to a computer screen